Uporaba hormonskih pripravkov v perimenopavzi v Sloveniji - Franić, Damir (Zdravniški vestnik, 2003)
Background. We want to collect data on the use of hormone therapy (HT) in perimenopausal women in Slovenia. These data were to serve as the basis for evaluation of the most frequently prescribed HT, and of the distribution of prescriptions by Slovene health regions. Consequently, the percent of women aged 40-65 years, current hormone replacement therapy (HRT) users was to be assessed. Methods. The analysis was made on the basis of the data collected bythe automatic processing of prescriptions (AOR). Reliability of the data hasbeen excellent since the introduction of the health insurance card. The data on drug use are expressed as defined daily doses (DDD) per 1000 inhabitants aged 40-65 years. The information on the number of women in a certain age group and their number in a certain medical region was obtained from the Statistical Institute of Slovenia and from the database of the Institute of Health Insurance of Slovenia. DDD is a tehnical unit, by means ofwhich drug use can be compared. DDD is a mean daily dose of the drug prescribed for the main indication in adults, the unit being 1 gram of the active substance. The AOR data have become reliable after 2001, therefore our analysis comparised the years 2001 and 2002. Comparison of the data was done using the list of drugs prepared according to the Anatomical Therapeutic Chemical classification (ATC) for coding drugs. Results. HRT (at least one pack) was found to be used by 12.5% of women in 2001 and 12.4% in 2002. The estimated percent of women in 2001 and 12.4% in 2002. The estimated percent ofwomen in 2001 and 12.4% in 2002. The estimated percent of women receiving HRT for at least 6 months was 6.5% in 2001 and 6.4% in 2002. (Abstract truncated at 2000 characters).
Keywords: Adult; Climacteric; Drug Utilization; Estradiol; Estrogen Replacement Therapy; Estrogen, nadomestno zdravljenje; hormonsko nadomestno zdravljenje; Klimakterij; Middle Age; Odrasli; Prescriptions, Drug; pripravki; Progestageni; Progestational Hormones; Recepti za zdravila; Slovenia; Slovenija; Srednja leta; Statistics And Numerical Data; Zdravilo, uporaba